MVP Expression Facilitates Tumor Cell Proliferation and Migration Supporting the Metastasis of Colorectal Cancer Cells - Paulina Pietras (MDPI AG, 2021)
Cancer cells show significant dysregulation of genes expression, which may favor their survival in the tumor environment. In this study, the cellular vault’s components MVP (major vault protein), TEP1 (telomerase-associated protein 1) and vPARP (vault poly(ADP-ribose) polymerase) were transiently or completely inhibited in U2OS cells (human bone osteosarcoma epithelial cells) to evaluate their impact on the cell proliferative and migratory capacity as well as on the development of their resistance to the drug vinorelbine. Comparative analysis of MVP protein expression level in normal colon tissue, primary colorectal tumor, and metastasis showed that the expression of this protein does not increase significantly in the primary tumor, but its expression increases in metastatic cells. Further comparative molecular analysis using the whole transcriptome microarrays for MVP-positive and MVP-negative cells showed that MVP is involved in regulating proliferation and migration of cancer cells. MVP may facilitate metastasis of colon cancer due to its impact on cell migration. Moreover, two vault proteins, MVP and TEP1, contribute the resistance to vinorelbine, while vPARP does not.